Konsep Pendidikan Ki Hajar Dewantara Ditinjau Dari Nilai-Nilai Religius Dan Relevansinya Dengan Kurikulum Merdeka - Rusadi, Bobi Erno; Munawaroh, Isnaini (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2024)
This research aims to find out and explain the religious values contained in Ki Hajar Dewantara's educational concept and determine the relevance of Ki Hajar Dewantara's educational concept to the independent curriculum regarding religious values. The method used in this research is a qualitative method based on a library research approach, which requires sources such as books, journals, articles and other literature relevant to the research title. The results of the research show that there is relevance between Ki Hajar Dewantara's educational concept in terms of religious values such as the value of tolerance in the pluralist education concept, the value of exemplary in the among concept, and the value of trust or responsibility in the tricentral concept of Ki Hajar education with the independent curriculum contained in the independent learning program, differentiated learning, and a project to strengthen the profile of pancasila students.